MODEL PEMBINAAN NARAPIDANA BERBASIS MASYARAKAT (COMMUNITY BASED CORRECTIONS) DALAM SISTEM PERADILAN PIDANA - H Hamja (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2015)
Community Based Correction is a type of coaching program for inmates as they live the rest of the sentence. They have been given the chance to return to society with a particular control or supervision. To implement the necessary operational program open prison five (5) basic principles, among others: the first principle prisoners should have the opportunity to obtain employment, the principle of the two prisoners must be selected first, third principle inmates should not be exploited, the fourth principle of security system should be a minimum, and The fifth principle of the transfer of responsibility for prisoners. Community Based Correction adalah jenis program pembinaan bagi narapidana sewaktu mereka menjalani sisa pidananya. Mereka diberi kesempatan untuk kembali ke tengah-tengah masyarakat dengan pengawasan atau supervisi tertentu. Untuk melaksanakan program operasional lapas terbuka diperlukan 5 (lima) prinsip dasar, antara lain: prinsip pertama narapidana harus memiliki kesempatan untuk memperoleh pekerjaan, prinsip kedua narapidana harus diseleksi terlebih dahulu, prinsip ketiga narapidana tidak boleh dieksploitasi, prinsip keempat sistem pengamanan harus minimum, dan prinsip kelima tanggung jawab pemindahan narapidana.